2019
DOI: 10.1002/pri.1764
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐machine interface of upper limb recovery in stroke patients rehabilitation: A systematic review

Abstract: Background Technologies such as brain‐computer interfaces are able to guide mental practice, in particular motor imagery performance, to promote recovery in stroke patients, as a combined approach to conventional therapy. Objective The aim of this systematic review was to provide a status report regarding advances in brain‐computer interface, focusing in particular in upper limb motor recovery. Methods The databases PubMed, Scopus, and PEDro were systematically searched for articles published between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 78 publications
0
33
0
1
Order By: Relevance
“…BCI training (BCIT) systems can use EEG signals from MI performance with sensory real-time feedback and decode these signals to enable patients to direct devices such as personal computers, wheelchairs, robots, and prosthetic devices including exoskeletons. Some studies have investigated the efficacy of applying BCIT using MI on motor recovery for patients with subacute or chronic stroke with hemiparesis [3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Although these studies demonstrated a significant effect on recovery, the studies were flawed by low number of participants, low number of training sessions and/or a lack of follow-up assessments [3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…BCI training (BCIT) systems can use EEG signals from MI performance with sensory real-time feedback and decode these signals to enable patients to direct devices such as personal computers, wheelchairs, robots, and prosthetic devices including exoskeletons. Some studies have investigated the efficacy of applying BCIT using MI on motor recovery for patients with subacute or chronic stroke with hemiparesis [3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Although these studies demonstrated a significant effect on recovery, the studies were flawed by low number of participants, low number of training sessions and/or a lack of follow-up assessments [3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we investigated how somatosensory abilities were taken into account and reported in the literature on BCI-based motor rehabilitation post-stroke. We assessed the papers that were cited in reviews focusing on BCI-based motor rehabilitation of the upper-limb ( Remsik et al, 2016 , Monge-Pereira et al, 2017 , Cervera et al, 2018 , Carvalho et al, 2019 , Bai et al, 2020 ). From the different papers cited we selected the 14 papers focusing on Randomized Clinical Trials (RCTs) of BCIs based on sensorimotor rhythms for post-stroke motor rehabilitation of the upper-limbs with different clinical trial registration number ( Ang et al, 2009 , Ang et al, 2010 , Ang et al, 2014 , Ang et al, 2015 , Biasiucci et al, 2018 , Frolov et al, 2017 , Li et al, 2014 , Mihara et al, 2013 , Pichiorri et al, 2015 , Ramos-Murguialday et al, 2013 , Rayegani et al, 2014 , Várkuti et al, 2013 , Wada et al, 2019 , Young et al, 2016 ).…”
Section: Bci Therapies For Motor Rehabilitation Post-strokementioning
confidence: 99%
“…Tiefere Einblicke in die Mechanismen, die einer Erholung zu Grunde liegen, könnten zu weiteren Fortschritten führen [27]. Die Präzision der Klassifizierung neurophysiologischer Aktivität durch das BCI könnte dabei eine wichtige Rolle spielen [28]. Eine relevante neurophysiologische Grundlage der Klassifizierung von Hirnsignalen könnte einen positiven Einfluss auf die Modulation der neuronalen Plastizität haben.…”
Section: Diskussionunclassified